Assembly of Natively Synthesized Dual Chromophores Into Functional Actinorhodopsin - Chuon, Kimleng; Kim, So Young; Meas, Seanghun; Shim, Jin-gon; Cho, Shin-Gyu; Kang, Kun-Wook; Kim, Ji-Hyun; Cho, Hyun-Suk; Jung, Kwang-Hwan (Frontiers in Microbiology, 2021)
Microbial rhodopsin is a simple solar energy-capturing molecule compared to the complex photosynthesis apparatus. Light-driven proton pumping across the cell membrane is a crucial mechanism underlying microbial energy production. Actinobacteria is one of the highly abundant bacterial phyla in freshwater habitats, and members of this lineage are considered to boost heterotrophic growth via phototrophy, as indicated by the presence of actino-opsin (ActR) genes in their genome. However, it is difficult to validate their function under laboratory settings because Actinobacteria are not consistently cultivable. Based on the published genome sequence of Candidatus aquiluna sp. strain IMCC13023, actinorhodopsin from the strain (ActR-13023) was isolated and characterized in this study. Notably, ActR-13023 assembled with natively synthesized carotenoid/retinal (used as a dual chromophore) and functioned as a light-driven outward proton pump. The ActR-13023 gene and putative genes involved in the chromophore (retinal/carotenoid) biosynthetic pathway were detected in the genome, indicating the functional expression ActR-13023 under natural conditions for the utilization of solar energy for proton translocation. Heterologous expressed ActR-13023 exhibited maximum absorption at 565 nm with practical proton pumping ability. Purified ActR-13023 could be reconstituted with actinobacterial carotenoids for additional light-harvesting. The existence of actinorhodopsin and its chromophore synthesis machinery in Actinobacteria indicates the inherent photo-energy conversion function of this microorganism. The assembly of ActR-13023 to its synthesized chromophores validated the microbial community's importance in the energy cycle.